A 3D controllable diffraction‐limited spot array generated by means of a spaced‐dipole array. Issue 2 (31st August 2021) - Yu, Yanzhong; Huang, Han; Lin, Shunda; Zeng, Yongxi; Chen, Musheng; Zhan, Qiwen
Abstract: The creation of an array of three‐dimensional (3D) multifocal spots in the focal region has attracted interest due to potential applications in parallel or simultaneous process areas. Based on the theory of pattern synthesis of antenna array and the electromagnetic time reversal technique, an optimisation‐free approach is reported to construct a 3D controllable diffraction‐limited spot array in the focal volume of a 4pi focussing system formed by two high‐numerical‐aperture (NA) objectives. The proposed method can be implemented readily by inversely focussing the field radiated from a virtual spaced‐dipole antenna array mounted at the focus of the 4pi configuration. By solving the inverse problem, the required illumination in the pupil plane for producing the 3D spot array can be found. It is demonstrated that the 3D diffraction‐limited focal spot array owns the properties of controllable polarisation, scheduled number, tunable location, and adjustable interval. This array may find applications in 3D simultaneous optical manipulation and trapping, 3D parallel fabrication, 3D optical data storage, and so on.